An Adapted Process and Organ Procurement Perspective on Heart Retransplantation for a Healthy Heart's Third Life. (September 2021) - Nethercot, Darryl C.; Shah, Mita; Stocks, Lisa M.; Trageser, Jeffrey M.; Pretorius, Victor; Morris, Gerald P.
As organ procurement organizations nationwide see an increased opportunity to retransplant already transplanted hearts, we would like to share the overview and process of our 2 successful cases. Heart retransplantation increased our cardiac placement rates by 2.64% and 2% in 2015 and 2019, respectively. Spread across a nation that sees over 3500 heart placements annually, a 2% increase would be substantial. Since 2009, our cases stand as the only documented heart retransplantations in the United States. However, United Network for Organ Sharing data shows that potential exists. From a facilitation perspective, we have developed a protocol to ease the matching process. From a surgical perspective, these cases had no complications and saved 2 lives, with each heart now beating in a third person. We hope that by sharing our process and success, we can familiarize fellow organ procurement organizations and transplant communities with this viable opportunity.